Inflation Inertia and the Optimal Hybrid Inflation/Price-Level Target - Øistein Røisland (Norges Bank, 2005)
A hybrid inflation/price-level target combines elements of both inflation and price-level targets. The paper derives a hybrid target within a new Keynesian model with inflation persistence due to price indexation. The result generalizes a result by Vestin (2005) that the optimal policy could be implemented with a price-level targeting regime. We show that the optimal price-level drift in the hybrid target is equal to the degree of price indexation.
hdl:11250/2498437
Keywords: E52; E61; E63; 330; price-level target; inflation persistence; commitment